Penerapan Pembelajaran Saintifik Model Social Inquiry untuk Meningkatkan Hasil Belajar IPS bagi Siswa Kelas VIII B SMP - Agus Sudarmono (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to improve: (1) presentation performance to students in social studies learning, and (2) social studies learning outcomes in the material